1963
DOI: 10.1126/science.141.3581.643
|View full text |Cite
|
Sign up to set email alerts
|

Sweating: Its Rapid Response to Muscular Work

Abstract: been purified approximately 300 fold by absorption and elution from diethylaminoethyl (DEAE) cellulose (12) followed by precipitation with 55-percent saturation of ammonium sulfate at 0?C. Moreover, when DEAE cel? lulose is developed with a linear NaCl gradient, the corresponding variant and normal LDH isozymes are eluted at similar points. The mobility of normal and variant LDH isozymes from crude hemolyzates is identical in the sys? tem (75) of varying starch-gel porosity. Such behavior suggests that the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 4 publications
5
54
0
Order By: Relevance
“…Mean skin temperature ( -Tsk) was calculated according to the method of Hardy & Dubois (1938). The SR on the three body sites was measured continuously by the ventilated capsule method (Van Beaumont & Bullard, 1963;Nadel et al 1971;Ogawa, 1975;Yamazaki et al 1994;Kondo et al 1998). Dry nitrogen gas was supplied to three capsules (chest and forearm: 7·06 cmÂ; palm: 1·53 cmÂ) at a rate of 1·5 l min¢ and the humidity of the nitrogen gas flowing out of the capsules was measured using a capacitance hygrometer (HMP 133Y; Vaisala, Finland).…”
Section: Measurementsmentioning
confidence: 99%
“…Mean skin temperature ( -Tsk) was calculated according to the method of Hardy & Dubois (1938). The SR on the three body sites was measured continuously by the ventilated capsule method (Van Beaumont & Bullard, 1963;Nadel et al 1971;Ogawa, 1975;Yamazaki et al 1994;Kondo et al 1998). Dry nitrogen gas was supplied to three capsules (chest and forearm: 7·06 cmÂ; palm: 1·53 cmÂ) at a rate of 1·5 l min¢ and the humidity of the nitrogen gas flowing out of the capsules was measured using a capacitance hygrometer (HMP 133Y; Vaisala, Finland).…”
Section: Measurementsmentioning
confidence: 99%
“…It has been demonstrated that at rest SCI athletes have warmer skin temperature, which enables an earlier onset of sweating, and therefore earlier skin cooling when compared with AB athletes. 16 This upper-body adaptation to an impaired thermoregulatory ability might help compensate for the lower body inability to dissipate stored heat.…”
Section: Discussionmentioning
confidence: 99%
“…In the palmar skin, it is well known that the sweating rate can increase without changes in the internal temperature [Kondo et al, , 1999Van Beaumont & Bullard, 1963, 1966. The changes in the sweating rate may be due to non-thermal factors involving activation of mechanosensitive or metabosensitive receptors in exercising muscles Van Beaumont & Bullard, 1963] or emotional or mental stimulation [Kuno, 1956].…”
Section: Introductionmentioning
confidence: 99%